Long-term trends in the burden of multiple myeloma in China: a Joinpoint regression and age-period-cohort analysis based on GBD 2021 - Yanyu Zhang; Quanxin Su; Jiawen Yu; Xiuli Sun (Frontiers in Public Health)
PurposeMultiple myeloma (MM) is a hematologic malignancy originating from plasma cells with clinical manifestations such as hypercalcemia, cytopenias (most commonly anemia) and renal failure. Here, we analyzed the disease burden and changing trends of MM in China from 1990 to 2021, aiming to provide a scientific and effective basis for the prevention and control of MM disease in China.MethodsWe extracted MM related data from the Global Burden of Diseases (GBD) 2021 database from 1990 to 2021. It is described according to incidence, prevalence, mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), years of life lost (YLLs) and other indicators. Using Joinpoint regression model to analyze the long-term trends of disease burden of MM in China. Using the age-period-cohort (apc) model to analyze the impact of age, period, and birth cohort on the burden of MM.ResultsIt is estimated that in 2021, there were 17,250 new cases of MM in China, with 47,004 cases and 12,984 deaths. The age-standardized incidence (ASIR), prevalence (ASPR) and mortality rates (ASMR) per 100,000 people were 0.81 (95% CI: 0.52, 1.07), 2.19 (95% CI: 1.37, 2.90) and 0.62 (95% CI: 0.40, 0.81), respectively. A comparison of ASIR, ASPR and ASMR in 2021 with those in 1990 indicated an increase. The ASIR and ASMR of males are higher than those of females overall, and both were increasing with age. The ASIR exhibited a gradual upward trend, while ASPR (AAPC = 6.43, 95% CI: 5.90, 6.96) demonstrated the most substantial increase. The apc model indicated the net drift was found to be 3.70% (95%CI: 3.32, 4.08%) per year for incidence and 2.57% (95%CI: 2.24, 2.89%) per year for mortality. The effects of age, period, and cohort on the incidence and mortality rates exhibited significant variations. The incidence risk increased with age, but the mortality risk showed fluctuations.ConclusionThe trends of MM disease burden in China continued to increase from 1990 to 2021. MM will be a major challenge for the future healthcare sector in China, where the population base is large and gradually aging.